Students’ Ability inVocabulary Mastery of English Education Major at Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tanjung Redeb - Nurbianta Nurbianta (ETERNAL (English Teaching Journal), 2018)
This paper mainly discusses the students’ ability in vocabulary mastery at SekolahTinggiIlmuTarbiyahMuhammadiyah (STITM) TanjungRedeb. The current paper draws presents the teaching and learning process by presenting the importance of plenty vocabulary mastery and the present situation where English plays important role in globalization era. The design study is proposed based on quantitative descriptive in STITM TanjungRedeb, Berau Regency of East Kalimantan. The participant was 19 students in second semester major in English education. The data collection was test and data analysis was scoring, mean, median, mode. The finding of this study was the performance on posttest show that the rating scale of students’ ability in vocabulary isvery good, the students obtained good ability.